Analysis Risk Factors of Asphyxia Neonatorum - Agustin Dwi Syalfina; Shrimarti Rukmini Devy (Jurnal Berkala Epidemiologi, 2015)
Antenatal care is an effort to promote, protect, and maintain maternal health during pregnancy and reduce maternal and infant mortality. The scope of antenatal care also includes the detection and treatment of pregnant women with high-risk cases and the detection and prevention of complications of pregnancy and childbirth. Complications of pregnancy and childbirth result in asphyxia neonatorum. The number of cases of asphyxia neonatorum in Mojokerto District was 46.9% in 2010 and 39.7% in 2014. The purpose of this study was to analyze the effect of antenatal care quality on asphyxia neonatorum in Mojokerto district. This type of observational analytic study was a case-control design with a large sample of cases and controls of 80 infants. Data were analyzed using univariate, bivariate, and multivariate analysis with logistic regression tests. The results of this study indicate that the quality of antenatal care has a significant effect on neonatal asphyxia (OR = 8,556; 95% CI: 2,777-26,358). Confounding variables that affect neonatal asphyxia are maternal occupation (OR = 4,558; 95% CI: 1,391–14,298), basic education (OR = 21,620; 95% CI: 1,932–241,886), secondary education (OR = 20,977; 95% CI : 1,819–241,872). Conclusion The quality of antenatal care influences neonatal asphyxia. A suggestion based on the results of this study is that health workers are expected to conduct health education to the community and family about the importance of antenatal care checks and antenatal care services that must be obtained from health workers.